Impact of Apocrine Gland Residue on Bromhidrosis Clinical Efficacy: A Self-controlled Case Series Study. Issue 5 (11th May 2022) - Lan, Shanshan; Zhao, Ziran; Wu, Di; Zheng, Chunmei; Dong, Xue; Zhang, Kejia
Abstract : Background: Apocrine sweat gland excision is a successful surgical treatment for bromhidrosis used in clinical practice due to its efficacy and unobtrusive postoperative scar. However, a small quantity of apocrine sweat gland residue is an unavoidable intraoperative concern to minimize losses of the dermal vascular network induced by extensive excision of the apocrine sweat glands. However, the relationship between the degree of remaining glands and clinical efficacy is yet unknown. This study looked at the histopathology of preexcision and postexcision specimens from bromhidrosis patients to see a connection between residual apocrine sweat glands and clinical efficacy following apocrine sweat gland excision. Methods: Twenty-one patients with bromhidrosis were recruited from April 2018 to December 2020. In this study, a description self-controlled case series was applied, with the patient preoperative sample as the control. The entire axillary skin was excised before and immediately after apocrine sweat gland excision, and skin tissue hemotoxylin-and-eosin staining was conducted to assess and compare the remnant apocrine sweat glands. Furthermore, preoperative and 6-month postoperative NRS-11 odor scores were analyzed, as well as patient satisfaction after surgery. Results: All patients had variable degrees of apocrine sweat gland excision residue, but they all passed clinical cure criteria and presented a high patient satisfaction rate. Conclusions: Apocrine sweat gland excision with a small quantity of apocrine sweat gland remnant can nevertheless result in a favorable clinical outcome and high patient satisfaction of bromhidrosis.